Pediatric traumatic brain injury: a new relation between outcome and neutrophil-to-lymphocite ratio - Marchese, Pietro; Lardone, Chiara; Canepele, Alessia; Biondi, Samanta; Roggi, Costantino; Massart, Francesco; Bonuccelli, Alice; Peroni, Diego; Giotta Lucifero, Alice; Luzzi, Sabino; Foiadelli, Thomas; Orsini, Alessandro (Acta Biomedica Atenei Parmensis, 2022)
ABSTRACTLeading causes of death in industrialized countries are traumatic injuries and acquired disability, and entry to the emergency department in childhood. TBI (traumatic brain injury) may involve the onset of both primary lesions and a complex immune response (sterile immune reaction to brain injury), which, in addition to neuro-protective effects, can mediate secondary neurological injury. The neutrophil-to-lymphocyte ratio (NLR), as a circulating inflammatory marker, has been related to outcomes in adult patients with non-neurologic diseases (such as gut tumours) or neurologic diseases (such as stroke or brain tumours), and to the prognosis of traumatic brain injury in adolescents and adults. However, the potential role of NLR in predicting outcomes in paediatric head trauma is not clearly defined. The aim of this retrospective observational study is to evaluate the association between clinical features predictive of intracranial and extracranial lesions in TBI and NLR and to establish whether an elevation of NLR is indirectly associated with adverse outcomes in pediatric patients with TBI. We analysed a sample of 219 pediatric patients, between 2-18 years old, after a TBI, and evaluated if differences in NLR were associated with neurological signs or positive CT in pediatric patients. We then compared the NLR values ​​between healthy subjects and patients with TBI.